AKIBAT HUKUM YANG TIMBUL TERHADAP KELALAIAN NOTARIS BERKAITAN DENGAN TANGGUNG JAWAB DAN KEWENANGANNYA (Studi Putusan Nomor 89/Pid.B/2020/PN.Dps) - Azhar, Mochammad Farras; Iriantoro, Agung (Jurnal Ilmiah Advokasi, 2025)
Notaries are public officials who must be guided by the norms and high virtues of the Indonesian people. Notaries in helping the community must have mutual trust between the parties so as to avoid mistakes, but Notaries are also ordinary people who are not free from mistakes whether intentional or unintentional or negligence. The result of that negligence can have an impact on the Notary and on the deed made by him. The method used in this research is normative juridical or also called doctrinal research, namely a study that analyzes the law both written in books and laws decided by judges through the courts. The theories used in this research are legal certainty theory and liability theory. The results of the research obtained: 1) The legal consequences arising from the negligence of a notary in the elements of forgery and malicious conspiracy in making a deed have an impact on the deed becoming null and void due to the absence of a lawful cause or not fulfilling the objective requirements of an agreement so that it can submit a deed cancellation. 2) Notaries must be responsible for their negligence in making deeds because it can harm one of the parties so that the Notary can be sanctioned administratively, criminally and civilly. If the Notary's actions have an element of intent, then the Notary can also be given administrative, criminal and civil sanctions. If the Notary's actions have an element of intentionality, then the Notary can be given criminal sanctions in the form of imprisonment and dishonorable dismissal from his position as a Notary. However, if the Notary did not commit intentionally or due to lack of prudence, then the sanctions given are only in the form of administrative sanctions such as reprimand or written sanctions. Keywords: Notary, Negligence, Forgery, Evil Conspiracy